Новый вид водяного клеща рода Atractides Koch. 1837 (Hygrobatidae, Acariformes) - Тузовский, П.В. (Вестник зоологии, 1977)
A new for science species of water mite Atractides virginalis (Hygrobatidae, Acariformes) is described, its picture is given.